Markers of healthy eating habits, water intake, and constipation in children between 4 and 7 years of age - ANDREOLI,Cristiana Santos (2018)
ABSTRACT Objective To evaluate the association between diet and constipation in children between four and seven years of age. Methods A cross-sectional study with 152 children between 4 and 7 years of age residing in Viçosa, Brazil. Constipation was defined in accordance with the Rome IV diagnostic criteria. Dietary habits were evaluated based on the frequency of food intake using a food diary for three days. Dietary analysis considered foods deemed healthy and unhealthy which could be associated with constipation, as well as the children’s consumption of fruits and vegetables. The amounts of fiber and water consumed were also rated as adequate or inadequate. As part of the analyses, Student’s t-test and the chi-square test were performed with a significance level of p<0.05. Results The prevalence of constipation was 32.2%. Constipation was more common among children who did not consume fruits (p=0.020) or greens (p=0.002), as well as among children who consumed “instant” chocolate drinks (p=0.033). An association was found between the frequent consumption of fried food (p=0.020), a daily water intake lower than 600mL, and constipation (p=0.028). Conclusion Unhealthy eating habits among children, such as the lack of fruit and greens intake and the consumption of “instant” chocolate drinks and fried foods, were found to be positively correlated with constipation. The low fruit and vegetable consumption observed herein reflects the need for changes in children’s eating habits and the implementation of measures to promote the intake of healthy foods.